2007
DOI: 10.1259/bjr/16282081
|View full text |Cite
|
Sign up to set email alerts
|

MR findings of pseudoneoplastic lesions in the uterine cervix mimicking adenoma malignum

Abstract: Pseudoneoplastic glandular lesions are benign lesions that are often histologically and radiographically confused with adenoma malignum, which is a rare variant of mucinous adenocarcinoma of the uterine cervix. 15 cases of pseudoneoplastic glandular lesions, characterized by multilocular cystic masses in the uterine cervix, were investigated; these lesions included endocervical glandular hyperplasia, deep nabothian cysts and tunnel cluster. All lesions were proven by conization or hysterectomy. The MR findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…AM is a rare carcinoma of the cervix with an estimated prevalence of 3% of all cervical adenocarcinomas and of 0.3% of all cervical carcinomas of the uterus [5]. The prognosis of AM is poor with lower survival rates than conventional adenocarcinoma because dissemination into the peritoneal cavity and distant metastasis occurs during the early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…AM is a rare carcinoma of the cervix with an estimated prevalence of 3% of all cervical adenocarcinomas and of 0.3% of all cervical carcinomas of the uterus [5]. The prognosis of AM is poor with lower survival rates than conventional adenocarcinoma because dissemination into the peritoneal cavity and distant metastasis occurs during the early stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the histopathological features of adenoma malignum are occasionally similar to pseudoneoplastic glandular lesions 16,17 . The MR findings of pseudoneoplastic lesions were almost identical to those of adenoma malignum, which suggested that the presence of cellular atypia or structural dysplasia in the pseudoneoplastic lesions did not significantly change MR findings 5,15 .…”
Section: Discussionmentioning
confidence: 78%
“…A preoperative punch biopsy fails to confirm a diagnosis of MDA in most cases 4 . Imaging study such as pulsed power Doppler and Magnetic Resonance Imaging are upcoming investigation modalities used for differentiating adenoma malignum from other cystic lesions of cevix [5][6][7] . Currently genetic markers linked to chromosome 19pl3.3 are found to be associated with the Sporadic Form of adenoma malignum of the uterine cervix 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Tunnel cluster is a specific type of Nabothian cyst characterised by complex multi cystic dilatation of endo cervical glands [4].…”
Section: Discussionmentioning
confidence: 99%